Robot-assisted axillary lymph node dissection in patients with node-positive breast cancer: techniques, learning curve, and preliminary results - Zhjie Wu; Zuxiao Chen; Zongyan Li; Xiaoyan Fu; Yunxiang Luo; Qiongyu Hu; Haiyan Li (The Lancet Regional Health. Western Pacific)
Background: Robot-assisted axillary lymph node dissection (RALND) has little application experience. In patients with breast cancer that have positive lymph nodes, we present the initial outcomes of RALND. Methods: We examined the medical records of individuals with breast cancer from a single institution that underwent RALND treatment between March 2024 and August 2024. The clinicopathological characteristics, learning curve, and consequences of RALND were investigated to determine the efficacy and safety of RALND. Findings: A total of 21 patients with RALND were included in the analysis. we reported that the Docking time took 8–10 minutes, and the average operation duration was 56.1 ± 14.6 min. After the accumulation of experience in 6 patients, the time required to complete RALND stabilized at about 60 minutes. The mean blood loss was 4.1 ± 2.1 mL, and the number of lymph nodes was 17.1 ± 5.6, of which 2.2 ± 3.5 were positive. All 21 patients had good shoulder joint movement (DASH score 10.82 ± 2.46), and no wound infection and lymphatic leakage were observed. Interpretation: According to our initial experience, RALND is a safe surgical procedure that can decrease intraoperative bleeding and the effect on upper limb function, lower the incidence of complications, and potentially be an alternative technique for treating patients with positive axillary lymph nodes in breast cancer.